Lego-Structured Tilting Table Method for Angle of Repose Measurement - putri, runita rizkiyanti (Liaison Journal of Engineering, 2024)
Flowability of solid material is important especially in food and pharmaceutical industry where solid material is the main material used. When designing equipment, understanding flowability of solid material becoming crucial point to maintain effectiveness of the equipment. Angle of repose is one of the oldest method to determine flowability of solid material. From several different method to measure angle of repose, tilting table method was chosen as the basis for this equipment design. Lego structure basis was chosen to modernized method for angle of repose measurement. For the experiment, 2 different materials were chosen: coriander seeds and cement powder. These 2 materials were chosen due to their different flowability properties to ensure the effectiveness of the designed equipment. From the measurement result, average angle of repost for coriander seed was 19.30 and 32.6o for cement powder. Based on these results, the percentage of error for angle of repost measurement using lego tilted structure equipment is between 6 until 20% which is in an acceptable level. This showed that the design of the equipment was a success and can be used to determine angle of repose of solid material. Keywords: Angle of repose, Flowability, Solid material, Lego, Solid properties